LANGUAGE MAINTENANCE (THE STUDY OF PAU SELLER ON JALAN SELAT PANJANG MEDAN) - Mangkey, Indriany; Laiya, Rebecca Evelyn (Universitas Nias Raya, 2023)
Tionghoa people in Medan are the Chinese who has already lived in Medan even in Sumatera in many years ago. All of the Tionghoa ancestors became a part of Indonesia and gave great contributions for Indonesia for ages. One of their contribution is to produce the Chinese culinary in one street in Medan. The purpose of the research is 1) to describe how the Pau sellerto maintain the Mandarin language and 2) to describe why the Pau sellers still maintain the Mandarin language. This research is the qualitative research. The researchers used the observation and interview to collect the data. The result of this research, the Pau sellers used many ways to maintain the mandarin language in their shops are 1) they use Mandarin Language to name their shops that is Siu Hua Kue Pau and under of that name they put the Mandarin Language 2) They also make the list of Pau by giving the kinds of Pau and also using the Mandarin Language.